2017
DOI: 10.1007/s12678-017-0442-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Glucose in Beverage Samples Using Poly(3,4-ethylenedioxythiophene)-Modified Electrodes with Immobilized Glucose Oxidase

Abstract: We developed two glucose biosensors based on poly(3,4-ethylenedioxythiophene) (PEDOT) and polyacrylic acid (PAA) doped with poly(4-lithium styrenesulfonic acid) (PSSLi) or PEDOT and anthranilic acid (AA) doped with poly(4-styrenesulfonic acid) (PSSH). The first one was already mentioned in literature in similar configurations; however, the second one has not been described before. The glucose oxidase was immobilized by means of covalent bonding, which has been proved by spectrophotometric assay with o-dianisid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Even though Ref. [ 7 ] presented a lower LOD than this work, their study used enzyme. Using enzyme electrochemical sensors allows very low detection limits and excellent accuracies.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Even though Ref. [ 7 ] presented a lower LOD than this work, their study used enzyme. Using enzyme electrochemical sensors allows very low detection limits and excellent accuracies.…”
Section: Resultsmentioning
confidence: 78%
“…Numerous articles described the use of the enzymatic electrochemical sensing technique for glucose detection in food and beverage samples [ 7 9 ]. Many of them focus on the construction and preparation of the sensors and their use for the determination of glucose in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…98%. A film composed of PEDOT, polyacrylic acid, and poly (4-lithium styrenesulphonic acid) PSSLi was electrodeposited on platinum electrode followed by GOx immobilization assisted with a carbodiimide [ 171 ]. Glucose determination was carried out into commercial juice and honey samples achieving a LOD of 290 μM with a linear range 9.6 × 10 −4 –3.0 × 10 −3 M. The same research group reported the synthesis of similar surfaces employing the same basic principles and optimizing the procedure of GOx immobilization [ 172 ].…”
Section: Electrochemical Sensors Based On Conducting Polymersmentioning
confidence: 99%
“…Glucose biosensor based on GOx, poly(3,4-ethylenedioxythiophene) (PEDOT) and anthranilic acid (AA) doped with poly(4-styrenesulphonic acid) (PSSH) was successfully applied for determination of glucose concentration in food samples such as grape juice and honey. 65 After a careful examination of the experimental data, it can be stated that the presented biosensor will be an appropriate tool for measurement of glucose concentration in food samples, provided that the concentration of ascorbic acid in such samples remains below the level of 0.1 mM.…”
Section: Amperometric Glucose Biosensorsmentioning
confidence: 99%
“…GOx + PEDOT + PAA + PSSLi 65 2.74 × 10 -4 A M -1 9.6 × 10 -4 -3 × 10 -2 Amp (2.9 × 10 -4 ) grape juice, GOx + PEDOT + AA + PSSH 65 (0.6 V) 2.57 × 10 -4 A M -1 1.86 × 10 -3 -3 × 10 -2 honey (5.6 × 10 -4 ) GOx + HRP + Fc 68 FIA, 10.7 nA mg -…”
Section: Amperometric Glucose Biosensorsmentioning
confidence: 99%